2017
DOI: 10.1083/jcb.201612030
|View full text |Cite
|
Sign up to set email alerts
|

Usher syndrome type 1–associated cadherins shape the photoreceptor outer segment

Abstract: Usher syndrome type 1 (USH1) causes combined hearing and sight defects, but USH1 protein function in the retina is unclear. Schietroma et al. use Xenopus to model the deficiency in two USH1 proteins—protocadherin-15 and cadherin-23—and identify crucial roles for these molecules in shaping the photoreceptor outer segment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(92 citation statements)
references
References 78 publications
8
83
0
1
Order By: Relevance
“…The Usher complex has been principally characterized in the inner ear where it forms 'tip-links' that connect adjacent stereocilia on the surface of mechanosensory hair cells (7). More recently, it has been proposed that the Usher complex also plays a role in organizing the actin-based microvilli-like calyceal processes that span the inner and outer segments of photoreceptor cells (8,9). Genetic disruption of components of the Usher complex results in Type 1 Usher Syndrome (USH1), a form of severe deafness-blindness in humans (10-16).…”
Section: Introductionmentioning
confidence: 99%
“…The Usher complex has been principally characterized in the inner ear where it forms 'tip-links' that connect adjacent stereocilia on the surface of mechanosensory hair cells (7). More recently, it has been proposed that the Usher complex also plays a role in organizing the actin-based microvilli-like calyceal processes that span the inner and outer segments of photoreceptor cells (8,9). Genetic disruption of components of the Usher complex results in Type 1 Usher Syndrome (USH1), a form of severe deafness-blindness in humans (10-16).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that CDH23 is expressed in the stereocilia of the hair cells of the inner ear at the region of the connecting cilia at the junction between the inner and outer segments [13]. Besides, CDH23 is also harbored in the retina [14] within the calyceal processes of the cone photoreceptors [15]. CDH23 contains 70 exons that encode for approximately 3354 amino acids and has a cDNA size of 10 kb (https://www.uniprot.org/uniprot/Q9H251).…”
Section: Discussionmentioning
confidence: 99%
“…fröschen, in denen Protocadherin 15 und Cadherin 23 herunterreguliert wurden, zeigen, dass beide USH-Cadherine für die Ausbildung der "calyceal processes" notwendig sind und ihr Fehlen zu Defekten in der Ausbildung und im Erhalt der Photorezeptoraußensegmente führt [49]. Weiterführende Erkenntnisse zur Funktion des USH-Netzwerkes in den "calyceal processes" sind von Nichtrodenten-USH-Säugermodellen, wie bspw.…”
Section: Funktion Der Ush-proteinnetzwerke In Haarsinneszellenunclassified